Hatchery capacity needed to support large‐scale Atlantic surfclam fishery enhancement - Caela B. Gilsinan; Sarah Borsetti; Daphne M. Munroe; Andrew M. Scheld (Aquaculture, Fish and Fisheries, 2024)
Abstract Fishery enhancement methods are being explored globally to sustain commercial and recreational fisheries through improving the productivity and management of marine populations impacted by anthropogenic stressors. It is expected that access to important Atlantic surfclam fishing grounds will be limited or lost due to growing overlap with offshore wind energy development. This study explores the economic viability of large‐scale hatchery production to improve fishery access and potentially offset additional costs, reduced revenues and potential job losses associated with the displacement of the fishing fleet. Reports and primary literature were used to understand the growth and survival of Atlantic surfclams in hatchery and nursery settings to calculate the scale of hatchery efforts needed to support one million (1M) bushels of fishery‐sized clams (>120 mm). Data on labour, energy, construction and material inputs and costs for hatchery and nursery production were gathered by analysing available literature and information provided by hatchery managers, researchers and others knowledgeable about shellfish hatchery production. A techno‐economic cost model and Monte Carlo analyses were employed to explore average costs and their variability. This study suggests that 374M–2.1B Atlantic surfclams are needed at the end of the hatchery stage to produce 1M bushels of market‐sized product. Total production costs range from $3.7 to $15.1M, including $2.9–$13.3M in hatchery costs and $800K–$1.9M in nursery costs. Under current market conditions, where Atlantic surfclams regularly sell for $14–$17/bushel, this analysis suggests that hatchery production could be considered a viable fishery enhancement method that supports human access to the fishery, though several additional questions remain.